Escaping into the World of Make-Up Routines in Iran. Issue 2 (May 2014) - Jafari, Aliakbar; Maclaran, Pauline
Traditionally, Iranian women's use of dress and make-up has been an arena – sometimes a battleground – for identity negotiation. The present study questions the current over-emphasis on identity and the prevalent tendency to look for identity meanings in the use of hejab (veiling) and cosmetics. The results of fifteen interpretive in-depth interviews with young adult women in Iran reveal that these individuals' make-up practices are largely associated with a total immersion in the experiential, creative aspects of make-up use and with ways to uplift their tired spirits in a monotonous environment. Make-up routines provide these women with opportunities to escape from boredom and immerse themselves in the playful fantasies of the world of cosmetics. Despite facing various challenges, including frequent stigmatization on account of their use of make-up, the informants in the study derive high levels of satisfaction from their make-up practices. The study establishes that changing socio-cultural dynamics give rise to new forms of consumption experiences in contemporary society and calls for further investigation of such experiences in women's everyday lives.